Understanding the determinants of sovereign debt ratings: evidence for the two leading agencies - Afonso, António (2022)
An analysis of the possible determinants of sovereign credit ratings assigned by the two leading credit rating agencies, Moody's and Standard and Poor's, is conducted in this paper by using linear, logistic, and exponential transformations of the rating scales. Of the large number of variables that can be used, the set of explanatory variables selected in this study is significant in explaining the credit ratings. Namely, six variables appear to be the most relevant to determining a country's credit rating: GDP per capita, external debt, level of economic development, default history, real growth rate, and inflation rate.